2016
DOI: 10.1136/postgradmedj-2015-133850
|View full text |Cite
|
Sign up to set email alerts
|

The patient who ‘must not be told’: demographic factors associated with collusion in a retrospective study in South India

Abstract: Collusion regarding diagnosis or prognosis is common among cancer patients referred for palliative care. It was more prevalent among female patients, manual workers, patients who had not received oncological treatment, and patients not accompanied by a spouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Prior studies have shown that 37% of advanced cancer patients in India had their prognosis withheld by family caregivers with resulting poorer QoL, and that those with poorer education were more likely to have prognosis withheld 31 . Collusion between professionals and families in India leads to prognosis being initially concealed for 40% of advanced cancer patients 32 . Our model illustrates the mechanisms and sequalae of these prior findings.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Prior studies have shown that 37% of advanced cancer patients in India had their prognosis withheld by family caregivers with resulting poorer QoL, and that those with poorer education were more likely to have prognosis withheld 31 . Collusion between professionals and families in India leads to prognosis being initially concealed for 40% of advanced cancer patients 32 . Our model illustrates the mechanisms and sequalae of these prior findings.…”
Section: Discussionmentioning
confidence: 57%
“…31 Collusion between professionals and families in India leads to prognosis being initially concealed for 40% of advanced cancer patients. 32 Our model illustrates the mechanisms and sequalae of these prior findings. Due to the well-recognized common challenges of late cancer presentation in India, the model addresses health literacy in relation to both diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 71%
“…Full texts of 126 articles were screened. A total of 27 studies fulfilled eligibility criteria and were thus eligible for inclusion in this systematic review and meta‐analysis 2,3,8‐32 . Table 1 shows the characteristics of included studies with the prevalence of collusion.…”
Section: Resultsmentioning
confidence: 99%
“…It is better to not give false optimism and screen for psychological distress more than syndromal diagnosis. [5] Each clinician can formulate words and phrases that capture paradox of uncertainty to sustain hope and honesty which might require certain level of communication skills in breaking bad news and dealing with collusion. After all, unraveling of the collusion can also help us to divert focus from body to soul and fits well in definition of healing in the Indian context.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the cultural context, collusion is divided into cultural collusion and familial collusion. [5]…”
Section: Introductionmentioning
confidence: 99%